Analysis of Formation Ronggojalu Spring and Probolinggo Active Fault Continuity with Satellite Data Gravity Method - M. Erfand Dzulfiqar Rafi; M. Haris Miftakhul Fajar; M. Singgih Purwanto; Anik Hilyah; Ayi Syaeful Bahri; Helda Kusuma Rahayu (Jurnal Penelitian Pendidikan IPA, 2023)
The Ronggojalu spring, with a discharge intensity of more than 3,000L/second, makes it one of the spring with the most significant discharge in Indonesia and is the main supplier of clean water for the City of Probolinggo. From the observation of topographic maps, the existence of this spring forms a lineament with Paras Spring and Sumber Kramat with a direction of Northeast to Southwest. The presence of this lineament can indicate the existence of geological structures that play a role in the formation of spring. In addition, this lineament is in the same direction as the active Probolinggo fault identified by PUSGEN (Pusat Studi Gempa Nasional). This study aims to identify the presence of geological structures in the lineament using satellite gravity data GGMplus (Global Gravity Model) and Remote Sensing. This data is quite efficient and effective in identifying subsurface geological structures. With the SVD (Second Vertical Derivative) analysis, the residual anomaly results from the second derivative value of the Bouger anomaly so that it can show the density contrast value as an indication of the geological structure. From the results of the interpolation of satellite gravity data in the study area, the CBA (Complete Bouguer Anomaly) value range is -16.8 – 4.8 mGal. The analysis of SVD and FHD shows a significant contrast different values along the fault line that passes through the spring. The lineament density processing also shows a weak zone around the fault zone, indicating the continuity in that zone. The existence of a fault under this spring indicates the influence of the fault on the formation of Ronggojalu Spring, Paras Spring, and Keramat Spring. In addition, it is estimated that this fault is a continuation of the active Probolinggo fault.